2018
DOI: 10.1186/s12887-018-1138-3
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse and neglect in the Jaffna district of Sri Lanka – a study on knowledge attitude practices and behavior of health care professionals

Abstract: BackgroundVictims and perpetrators of child abuse do not typically self-report to child protection services, therefore responsibility of detection and reporting falls on the others. Knowledge on child protection is essential for the first contact person and such information is sparse in research literature originally coming from Sri Lanka. Anecdotally, several cases of child abuse have been missed out at the first contact level. Therefore we undertook this survey to assess the knowledge, attitudes towards chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 17 publications
2
25
1
5
Order By: Relevance
“…This did not seem to disagree with our results, as we observed that specialty significantly influences the knowledge score, with pediatricians exhibiting lower knowledge scores than doctors in other specialties. However, our results contradict the report by Sathiadas et al, who found that the knowledge, attitude, and behavior of healthcare professionals toward child abuse were significantly good among respondents within the pediatric specialty [ 18 ]. Similarly, we also noted that physicians with children have significantly better KA scores than those without children.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This did not seem to disagree with our results, as we observed that specialty significantly influences the knowledge score, with pediatricians exhibiting lower knowledge scores than doctors in other specialties. However, our results contradict the report by Sathiadas et al, who found that the knowledge, attitude, and behavior of healthcare professionals toward child abuse were significantly good among respondents within the pediatric specialty [ 18 ]. Similarly, we also noted that physicians with children have significantly better KA scores than those without children.…”
Section: Discussioncontrasting
confidence: 99%
“…The study showed that the main obstacles to reporting such cases were the fear of misdiagnosis and the fear of separating the children from their families with a lack of knowledge about the reporting process [ 8 ]. Sathiadas et al [ 18 ] reported that although healthcare professionals demonstrated good overall knowledge, 65.8% of physicians were unsatisfied with their knowledge and expressed the desire for some form of education on child maltreatment to further their understanding. AlBakr et al [ 16 ] reported that the overall knowledge among all primary healthcare physicians in Al-Khobar City in the Eastern Region of Saudi Arabia about child abuse was significantly higher among those aged 36-40 years, which aligned with our findings related to the age of the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…while some of the increases in reporting may be due to a greater availability of helpdesks, fieldlevel research also confirmed perceptions that a growing number of children are facing issues of malnutrition, abuse, and abandonment. In addition, reports of child abuse, neglect, and exploitation are likely underreported, in part because of sociocultural factors (Sathiadas, Viswalingam, and Vijayaratnam 2018).…”
Section: Vulnerable Populationsmentioning
confidence: 99%
“…A number of studies (11)(12)(13)(14)(15) point out relevant factors that permeate the intervention by nurses in cases of violence in the pediatric and adolescent population, such as the reason for the silence established in the family, the fear coming from the professionals for having doubts about tangible problem solving, definition of care protocols and flows, professional training, lack of resoluteness by the child protection agencies and lack of institutional and governmental support to deal with these families (16) .…”
Section: Introductionmentioning
confidence: 99%